A randomized pilot study to evaluate graft versus fistula vascular access strategy in older patients with advanced kidney disease: results of a feasibility study - Mariana Murea (Pilot and Feasibility Studies, 2020)
Abstract Background Although older adults encompass almost half of patients with advanced chronic kidney disease, it remains unclear which long-term hemodialysis vascular access type, arteriovenous fistula or arteriovenous graft, is optimal with respect to effectiveness and patient satisfaction. Clinical outcomes based on the initial AV access type have not been evaluated in randomized controlled trials. This pilot study tested the feasibility of randomizing older adults with advanced kidney disease to initial arteriovenous fistula versus graft vascular access surgery. Methods Patients 65 years or older with pre-dialysis chronic kidney disease or incident end-stage kidney disease and no prior arteriovenous vascular access intervention were randomized in a 1:1 ratio to undergo surgical placement of a fistula or a graft after providing informed consent. Trial feasibility was evaluated as (i) recruitment of ≥ 70% of eligible participants, (ii) ≥ 50 to 70% of participants undergo placement of index arteriovenous access within 90 to 180 days of enrollment, respectively, (iii) ≥ 80% adherence to study-related assessments, and (iv) ≥ 70% of participants who underwent index arteriovenous access placement will have a follow-up duration of ≥ 12 months after index surgery date. Results Between September 2018 and October 2019, 81% (44/54) of eligible participants consented and were enrolled in the study; 11 had pre-dialysis chronic kidney disease, and 33 had incident or prevalent end-stage kidney disease. After randomization, 100% (21/21) assigned to arteriovenous fistula surgery and 78% (18/23) assigned to arteriovenous graft surgery underwent index arteriovenous access placement within a median (1st, 3rd quartile) of 5.0 (1.0, 14.0) days and 13.0 (5.0, 44.3) days, respectively, after referral to vascular surgery. The completion rates for study-specific assessments ranged between 40.0 and 88.6%. At median follow-up of 215.0 days, 5 participants expired, 7 completed 12 months of follow-up, and 29 are actively being followed. Assessments of grip strength, functional independence, and vascular access satisfaction were completed by > 85% of patients who reached pre-specified post-operative assessment time point. Conclusions Results from this study reveal it is feasible to enroll and randomize older adults with advanced kidney disease to one of two different arteriovenous vascular access placement surgeries. The study can progress with minor protocol adjustments to a multisite clinical trial. Trial registration Clinical Trials ID, NCT03545113 .